Proposed business model innovation of pt daya sentosa utama in regards to regulation and its sustainability - Aji Soedibyo, Bayu; Hamsal, Mohamad (The Indonesian Journal of Business Administration, 2016)
Abstract – PT Daya Sentosa Utama is a private company engaged in big bus public transport’s operator in Jakarta since 2003. Nowadays with the establishment of Regulation PERDA DKI Jakarta 5/2014 on article 51 stated that big bus public transport will operationally legitimate for only its first 10 years. Due to ineffectiveness of its implementation, the company should be proactively and dynamically managing towards the effectiveness of the regulation in order for the company to be sustaining in the future. The company’s sustainability is the main focus of the research. Thus the big bus public transport industry in Jakarta is heading down due to unjust competition, enhancement operational reliability and conveniences of the substitute products, high operating expenditure and lesser passenger throughput. Resulting to the competitor had suffered losses in 3 straight years from 2013 with current revenue averaging per day per unit only up to IDR 300,000. In order to revive business solutions, external and internal assessment is performed priory. PESTEL Analysis, Competitor and Industrial structure and Porter’s Five forces is utilized to describe external environment that encounter by the company. Value Chain, Resource Based and Business Model Canvas along with digested information from qualitative primary data utilized to indentify and define the company’s current business model along with its social situation. The company current’s phase defines into type of business model innovation’s degree based on Mitchell and Coles (2003) integrated framework. The next step is formulating that using business model canvas with focusing on customer-driven which generate direct conversation to end users and offer-driven innovation which generate new stream line of revenue models. Lastly is implementation plan. The implementation performed into three stages which comprising of preparation, execution and evaluation. Therefore, the proposed business model innovation must be tested and proven in the company towards changes in regard to regulation and challenges in regard to the company’s sustainability. Keywords: Regulation, Sustainability, Business Model Innovation, Big Bus Public Transport